Barthes: A very short introduction - Culler, Jonathan (Oxford Oxford university press, 2002)
Roland Barthes was the leading figure of French Structuralism, the theoretical movement of the 1960s which revolutionized the study of literature and culture, as well as history and psychoanalysis. But Barthes was a man who disliked orthodoxies. His shifting positions and theoretical interests make him hard to grasp and assess. This book surveys Barthes' work in clear, accessible prose, highlighting what is most interesting and important in his work today. In particular, the book describes the many projects, which Barthes explored and which helped to change the way we think about a range of cultural phenomena--from literature, fashion, wrestling, and advertising to notions of the self, of history, and of nature.